The Neurodiverse Classroom : a Teachers' Guide to Individual Learning Needs and How to Meet Them. - Honeybourne, Victoria (Jessica Kingsley Publishers, 2018)
This book enables teachers to meet the needs of children with a wide range of specific learning difficulties in mainstream classrooms, while promoting acceptance and self-esteem. Viewing the class as a diverse group rather than focusing on diagnoses, it presents advice and strategies for creating a supportive learning environment for all.